Impact of Loyalty Card on Philippine Retail Industry - Palma, Norvin M. (IJRDO - Journal of Business Management, 2017)
The goal of this paper is to know the impact of the loyalty card in the Philippine Retail Industry. The paper will show the value of the card to the different aspect in business. It also entails to tackle about the contributions of the card to the customer perspectives and business acumen. It has characterized about the decision basis regarding purchase of the products vis a vis to the loyalty card. It also enables the advantage of bringing the card to the retail industry. This paper signifies the result of using the card to the purchase transactions, redemption of points, and effect to the different business departments. The results will contribute to the attainment of Key Performance Indicator or measurement of a retail company contributing in sales, repeat transactions, and other key success factor. On contrary aspect, it might expose the negativism about the inactive users particularly the discontinuity of the usage of the card regarding the process and dissatisfaction of the users.